A global assessment of the relationship between anthropogenic debris on land and the seafloor. (September 2020) - Roman, Lauren; Hardesty, Britta Denise; Leonard, George H.; Pragnell-Raasch, Hannah; Mallos, Nicholas; Campbell, Ian; Wilcox, Chris
Abstract: Pollution of coastal and marine environments by mismanaged anthropogenic debris is a global threat requiring complex, multilateral solutions and mitigation strategies. International efforts to catalogue and quantify the density, extent and nature of mismanaged waste have not yet assessed the heterogeneity of debris between nearby areas. Better understanding of how debris types and density can be used as a proxy between regions and between land and seafloor habitats at a global scale can aid in developing cost effective and representative debris monitoring systems. Using volunteer collected clean-up and survey data, we compared the proportion and density of both total debris and specific items across 19, 428 coastal land and seafloor sites from International Coastal Cleanups and Dive Against Debris surveys, from 86 countries between 2011 and 2018. We show that although some items common on land are also common on the seafloor, there is an overall global mismatch between debris types and densities on land and the seafloor from nearby areas. Correlations in land/seafloor debris type/density occurred primarily for items which entangle and/or sink, including fishing line, plastic bags, glass and polyethylene terephthalate (PET) bottles. Minimal similarity between land and seafloor surveys occurs for items which float or degrade. We suggest that to accurately evaluate local debris density, land and seafloor surveys are required to gain a holistic understanding. When detailed information on debris type, relative concentration, and likely source and transport are assessed, more cost effective and efficient policy interventions can be designed and implemented from local through to global scales. Graphical abstract: Image 1 Highlights: First global analysis of coastal debris across land and seafloor habitat. Assess 42 different items across 19, 428 land and seafloor sites in 86 countries. Items common on land tend also to be common on the seafloor overall. Overall debris type and density mismatch between adjacent land and seafloor. To accurately evaluate local debris, both land and seafloor surveys required. Abstract : Debris items are globally heterogeneous, and though some items common on land are also common on the seafloor, there is an overall global mismatch between debris types and densities on land and the seafloor from nearby areas. Correlations in land/seafloor debris type/density occurred primarily for items which entangle and/or sink, with low correlation for floating items, with implications for debris survey methodology and policy interventions.